UPAYA PENINGKATAN AKTIVITAS SISWA PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI SMP NEGERI 7 MUARA BUNGO TAHUN PELAJARAN 2017/2018 - Zuryati Zuryati (LP3M Universitas Muhammadiyah Muara Bungo, 2019)
This research is based on the activities of students in PKn learning who are less actively participating because there is only the provision of information from teacher to student. So that students are less enthusiastic and look biased during the learning process. This study aims to improve the activity of students in PKn learning through the Contextual Teaching and Learning (CTL) approach in class IX1 Even semester 2017/2018 students at SMP Negeri 7 Muara Bungo. This type of research is classroom action research (CAR) with a qualitative descriptive approach carried out in two cycles. The results showed that the application of Contextual Teaching and Learning in Civics learning can increase student activity by 82.8% or an average of 5.88. student learning activities increased from cycle I to cycle II including a) ability to answer questions 26.6%, b) submit questions 14.8%, c) ability to express opinions 17.7%, d) skills in giving suggestions 8.9% and e) ability to express conclusion of 14.8%.